Genetic diversity analysis among Philodendron spp. by Random Amplified Polymorphic DNA - Karmawan, Listya Utami; Gunawan, Renaldy (Biogenesis: Jurnal Ilmiah Biologi, 2024)
Variety development in ornamental plants increased rapidly due to the high demand during the COVID-19 outbreak. Therefore, analyzing the genetic diversity of ornamental plants is essential to assist breeders in improving and developing new cultivars with desirable traits. In this study, the genetic diversity of Philodendron species was analyzed. P. erubescens, P. 69686, P. burle-marx, P. lacerum, and P. micans were selected as the most popular species cultivated in Indonesian nurseries. These cultivars were assessed both genetically using Random Amplified Polymorphic DNA (RAPD) markers and morphologically. The genetic relationship among Philodendron spp. species was analyzed using DARwin 6.0 software, and a dendrogram was constructed based on the UPGMA algorithm. Based on the two selected RAPD primers, the five samples showed no clear genetic relatedness to each other, and the primers were insufficient to construct a single consensus dendrogram.